1996
DOI: 10.1002/j.2168-9830.1996.tb00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Revising a Mechanical Engineering Curriculum: The Implementation Process

Abstract: In early 1990, motivated largely by concern for the highly structured nature of engineering education, the faculty of Purdue's School of Mechanical Engineering initiated a two‐year assessment of its curriculum. A principal conclusion of this assessment was that students should have more exposure to open‐ended, cross‐functional problems and that design, interpreted broadly, provided the best platform for launching appropriate curriculum changes. Specific plans for curriculum revision included a) early exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Anything goes, so you have to see what you have first.Students' beliefs in the difference between classroom and workplace problems aligns with other studies that have examined the structures of these problems. Jonassen et al () found that one of the primary characteristics of workplace problems is that they are ill‐structured, whereas most classroom problems are well structured and have only one correct solution (Incropera & Fox, ; Sheppard et al, 2009). Regarding the difference in structure between classroom and workplace problems, Sheppard et al (2009) argued that “Solving right‐answer problems is not necessarily problem solving: the problems that students are typically asked to solve do not build the kind of problem‐solving skills they will need later in their program or in practice” (p. 48).…”
Section: Discussionmentioning
confidence: 99%
“…Anything goes, so you have to see what you have first.Students' beliefs in the difference between classroom and workplace problems aligns with other studies that have examined the structures of these problems. Jonassen et al () found that one of the primary characteristics of workplace problems is that they are ill‐structured, whereas most classroom problems are well structured and have only one correct solution (Incropera & Fox, ; Sheppard et al, 2009). Regarding the difference in structure between classroom and workplace problems, Sheppard et al (2009) argued that “Solving right‐answer problems is not necessarily problem solving: the problems that students are typically asked to solve do not build the kind of problem‐solving skills they will need later in their program or in practice” (p. 48).…”
Section: Discussionmentioning
confidence: 99%
“…They require design in two or three different courses. This emphasis reflects the pre-2000 engineering accreditation requirement for a specific number of credits of design content, the ABET engineering outcomes, and numerous other recommendations for design in the engineering curriculum [26][27][28][29][30][31].…”
Section: July 2006mentioning
confidence: 99%
“…The challenge of working on industrial problems (and projects), and in close contact with architects and engineers who (themselves) are concurrently working on the same or similar problems (and projects), provides valuable experience which can ease the post-graduate transition from student to employee [6].…”
Section: Connected Curriculum: a More Integrated Professionmentioning
confidence: 99%